The correlation of bedside ultrasound inferior vena cava distensibility index with pulse pressure variation and central venous pressure in ventilated sepsis patient in assessing fluid status in intensive care unit Hospital Universiti Sains Malaysia - Mazlan, Mohd Zulfakar (2015)

(untitled)
Introduction: Inferior vena cava (IVC) distensibility index, pulse pressure variation (PPV), and central venous pressure (CVP) are known to be important variables in assessing fluid status of critically ill patients. A study showed that CVP is a poor predictor of fluid status. Objectives: The aim of this study is to determine the relationship between Inferior vena cava (IVC) distensibility index, PPV and CVP with adult ventilated septic Intensive Care Unit (ICU) patients in assessing fluid responsiveness. Methods: A cross sectional study was done to 67 ventilated adult sepsis patients admitted to ICU Hospital Universiti Sains Malaysia (HUSM) from April 2014 until November 2014. Inferior vena cava (IVC) distensibility index was measured by bedside ultrasound machine, PPV calculated manually and CVP was directly measured. Results: There was a fair correlation between Inferior vena cava (IVC) distensibility index and PPV (r= 0.49, p- value <0.001. However there was no significant correlation between Inferior vena cava (IVC) distensibility index and CVP and between PPV and CVP. Conclusion: Therefore, Inferior vena cava (IVC) distensibility index and PPV was useful as a dynamic tool of measurement of fluid responsiveness in critically ill patient.